Various approaches of color feature extraction in leaf diseases under image processing: a survey - Eaganathan, Umapathy; S. Prasanna, Dr; Sripriya, Dr (International Journal of Engineering and Technology, 2018)
The detection of plant leaf disease is one of the major challenging tasks to prevent serious outbreak in the field of agriculture. Feature Ex-traction is one of the important techniques in digital image processing for simplifying the amount of resources required to explain a bulk set of data accurately. In image processing, image features normally include color, shape and texture features. Some researches made combina-tion of color and texture features used to recognize and classify leaf diseases. Mostly color is a widely used features obtained by different methods in feature extraction and respectively used to distinguish diseases in leaf. One of the difficulty in feature extraction based on color consumes more time to identify or classify the diseased part is the tricky one. The diseased leaf not exactly identified from its characteristics so the color feature extraction technique is used to identify the optimum that could differentiate between the target object and background of the leaves. Various color model combinations has been followed earlier for extracting the diseased spot from the leaf is discussed here. This paper also explains the performance comparison of different existing color based feature extractions.Â Â